The Tri Kaya Parisudha-Based SFAE Learning Model Has A Positive Impact on Fifth-Grade Students' Science Knowledge Competencies - Putri, Ni Komang Ayu Triana; Wiarta, I Wayan (Universitas Pendidikan Ganesha, 2023)
Learning that takes place, especially science subjects, is different from the mandate of the 2013 curriculum. The science knowledge competence of elementary school students still needs to improve. This study aims to analyze the effect of the SFAE learning model based on Tri Kaya Parisudha on students' science knowledge competence. This type of research is a quasi-experiment using a nonequivalent control group design. The population of this study was all grade V students, as many as 443 students, with sample determination using a cluster random sampling technique. The data collection method used an essay-type test. The research data were analyzed using descriptive statistical techniques and inferential statistical analysis (t-test). The results of hypothesis testing using the t-test technique with polled variance formula obtained a t-count equal to 4.67 more than the t-table equal to 1.998 at a 5% significance level with dk equal to 63, so Ha is accepted, and H0 is rejected. So it is concluded that the SFAE learning model based on Tri Kaya Parisudha affects students' science knowledge competence. This research implies that the SFAE learning model based on Tri Kaya Parisudha is expected to be an innovative learning model to encourage student activeness and improve learning outcomes.